The classic horror stories - Lovecraft, H. P. (Howard Phillips) 1890-1937; Luckhurst, Roger (Oxford, United Kingdom Oxford University Press, 2013)
H. P. Lovecraft (1890-1937) was a reclusive scribbler of horror stories for the American pulp magazines that specialized in Gothic and science fiction in the interwar years. He often published in Weird Tales and has since become the key figure in the slippery genre of "weird fiction." Lovecraft developed an extraordinary vision of feeble men driven to the edge of sanity by glimpses of malign beings that have survived from human prehistory or by malevolent extra-terrestrial visitations. The ornate language of his stories builds towards grotesque moments of revelation, quite unlike any other writer.
Horror at Red Hook --Call of Cthulhu -- Colour out of space -- Dunwich horror -- Whisperer in darkness -- At the mountains of madness -- Dreams in the witch-house -- Shadow over Innsmouth -- Shadow out of time.
Includes bibliographical references.
Keywords: Horror tales, American; Short stories; Horror fiction